Slovak Whistleblowing Law after Revision – a Step Forward? - Varga, Peter; Zoričáková, Veronika (Towards a Better Protection of Workplace Whistleblowers in the Visegrad Countries, France and Slovenia, 2021)
In this chapter, the authors try to analyse the main aspects of the new Slovak Act on whistleblower protection No. 54/2019 Coll. Firstly, the authors highlight the fact that although Slovakia has a specialized Act regulating whistleblowing, other applicable legislation exists, as well. As it turns out, the antidiscrimination legislation still plays an important role, as the new Slovak Act does not cover all cases of whistleblowing protection. Furthermore, the authors analyse the personal and material scope of the provided protection and contemplate the connection between the definition of the whistleblower and the protection provided pursuant to the new Act. With regards to the material scope of protection, the act distinguishes between two kinds of anti-social activities depending on their severity. As it turns out, protection pursuant the new Act is provided only to whistleblowers reporting more serious anti-social activities. In other cases, the antidiscrimination legislation is the only platform for protection of such notifiers. Lastly, the new Act establishes both internal and external channels for reporting anti-social activities, with the new established Office for the Protection of Whistleblowers playing an important role. Although the Office is more or less only an administrative and monitoring body, it also grants specialized ex ante and ex post protection directly in labour law employer-employee relations and closely cooperates with relevant authorities competent for investigating criminal or administrative offences.